Literatura e instituição: Cenários da responsabilidade e da hospitalidade - Villa Da Silva, Maria Das Graças Gomes [UNESP] (My University, 2004)
In this essay, the objective is to show some crucial moments related to the theme literature and institution to emphasize the effects and difficulties that resulted from the transformations occurred in the study of the institutionalized literature and also to encourage the reflection about those changes, highlighting the need for transformation and for provoking serious thinking about those alterations.
Literature and institution: Sceneries of responsibility and hospitality
Keywords: Hospitality; Institution; Literature; Reflection; Responsibility; Transformation